Conductivity enhancement in AlGaN:Mg by suppressing the incorporation of carbon impurity. (7th April 2015) - Tian, Aiqin; Liu, Jianping; Ikeda, Masao; Zhang, Shuming; Li, Zengcheng; Feng, Meixin; Zhou, Kun; Li, Deyao; Zhang, Liqun; Wen, Pengyan; Zhang, Feng; Yang, Hui
Abstract: Growth conditions were explored to suppress the carbon impurity incorporation in AlGaN:Mg grown at low temperatures. Electrical properties of Al0.07 Ga0.93 N:Mg samples with various carbon concentrations were investigated by Hall measurements. A clear correlation between carbon concentration and electrical conductivity has been found. By reducing the carbon concentration from 2 × 10 18 to 5 × 10 16 cm −3, the resistivity of p-Al0.07 Ga0.93 N decreases from 7.4 to 2.2 Ω·cm. From the results of the analysis of the charge neutrality equation, we found that the carbon concentration is close to the compensating donor concentration in the AlGaN:Mg samples, which suggests that carbon acts as the main compensating donor in AlGaN:Mg.